2019
DOI: 10.1039/c9nr05954g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine PtCuRh nanowire catalysts with alleviated poisoning effect for efficient ethanol oxidation

Abstract: A robust and universal seed-mediated growth method has been developed for making a series of ultrafine PtCuM (M = Rh, Pd, Ir) alloy nanowires, which show greatly improved electrocatalytic performance for ethanol oxidation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…One of the most efficient methods to regulate the electronic structure of Pt is to introduce a second or more metal elements into Pt to form a perfect alloy structure, where the d-band center can be effectively downshifted, resulting in a favorable electronic environment for catalytic reactions that can enhance catalytic properties. [46][47][48][49][50] Recently, our group has reported the successful regulation of the Pt electronic structure of Pt by fabricating ternary PtCuRh UNWs, [51] in which the addition of Cu and Rh significantly affected the electronic structure of Pt, resulting in the optimized adsorption strength of reactants on the surface of PtCuRh UNWs and a significantly enhanced electrocatalytic performance. Moreover, Guo's group [52] reported the synthesis of a series of well-defined PtNiM (M = Rh, Os, and Ir) UNWs for electrocatalytic alcohol oxidation, where the strong electronic effect among Pt, Rh (Os and Ir), and Ni contributed to the formation of weak PtCO bonding, thereby resulting in excellent CO-tolerance and electrocatalytic properties.…”
Section: Electronic Structure Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most efficient methods to regulate the electronic structure of Pt is to introduce a second or more metal elements into Pt to form a perfect alloy structure, where the d-band center can be effectively downshifted, resulting in a favorable electronic environment for catalytic reactions that can enhance catalytic properties. [46][47][48][49][50] Recently, our group has reported the successful regulation of the Pt electronic structure of Pt by fabricating ternary PtCuRh UNWs, [51] in which the addition of Cu and Rh significantly affected the electronic structure of Pt, resulting in the optimized adsorption strength of reactants on the surface of PtCuRh UNWs and a significantly enhanced electrocatalytic performance. Moreover, Guo's group [52] reported the synthesis of a series of well-defined PtNiM (M = Rh, Os, and Ir) UNWs for electrocatalytic alcohol oxidation, where the strong electronic effect among Pt, Rh (Os and Ir), and Ni contributed to the formation of weak PtCO bonding, thereby resulting in excellent CO-tolerance and electrocatalytic properties.…”
Section: Electronic Structure Regulationmentioning
confidence: 99%
“…Based on the analyses above, designing and synthesizing 1D Pt‐based UNWs is crucial for improving the breaking ability of CC bonds, which is favorable for promoting the electrocatalytic EOR performance; therefore, researchers are keen to explore efficient EOR electrocatalysts. [ 51 ] For example, Zhu et al [ 88 ] reported the successful fabrication of subnanometer Pt–Rh UNWs with tunable compositions ( Figure a), in which optimized PtRh UNWs exhibited superior antipoisoning ability and displayed significantly enhanced CC breaking ability with an important C1 pathway selectivity for EOR (Figure 5b–g). The significant enhancement in electrocatalytic EOR performance can be ascribed to the multiple merits of high atom utilization efficiency and accelerated electron transfer from the unique 1D nanostructure (Figure 5h).…”
Section: Applications Of Pt‐based Unws For Advanced Catalysismentioning
confidence: 99%
“…Three broad peaks centered at 38.9 o , 45.2 o and 66.5 o were detected for Pt 2 Sn/NG catalyst (Fig. 1), owing to the reflections of (111), ( 200) and (220) planes of Pt NPs with face-center cubic (fcc) structure, respectively 40 The transmission electron microscopy (TEM) was further performed to investigate the structure evolution of the thermal treatment of Pt 2 Sn/NG sample. Fig.…”
Section: Structure Of the Catalystmentioning
confidence: 99%
“…Consequently, it is urgent to find an efficient catalyst to lower the activation energy of the reaction to make the fuel cell better applied [13–16] . Although Pt was confirmed as an excellent electrocatalyst, it is not suitable for large‐scale use owing to its low storage [17–20] . Great efforts have transferred to seek for other alternative catalysts, like Pd, the same family as Pt, which has attracted great interests in recent years [21–26] …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Although Pt was confirmed as an excellent electrocatalyst, it is not suitable for large-scale use owing to its low storage. [17][18][19][20] Great efforts have transferred to seek for other alternative catalysts, like Pd, the same family as Pt, which has attracted great interests in recent years. [21][22][23][24][25][26] Aiming to improve the catalytic ability, a large number of experiments have been conducted to find stable alloyed palladium-based binary nanostructured catalysts (PdÀ Au, [27][28][29][30][31] PdÀ Co, [32][33][34] PdÀ Ni, [35,36] PdÀ Cu, [37][38][39][40] PdÀ Ag, [41][42][43][44][45] etc.)…”
Section: Introductionmentioning
confidence: 99%